Analytical figures of merit of a low-dispersion aerosol transport system for high-throughput LA-ICP-MS analysis. Issue 6 (12th May 2021) - Van Acker, Thibaut; Van Malderen, Stijn J. M.; Van Helden, Tom; Stremtan, Ciprian; Šala, Martin; van Elteren, Johannes T.; Vanhaecke, Frank
Abstract : This work reports on the analytical performance of a LA-ICP-MS low-dispersion aerosol transport system coupled to a two-volume ablation cell and a low-dispersion ablation cell housed in a LA-unit equipped with a nanosecond 1 kHz lasing system. Abstract : This work reports on the analytical figures of merit of a low-dispersion aerosol transport system for high-throughput bulk and spatially resolved analysis via LA-ICP-MS. This device maximizes the collection of aerosol particles generated during the ablation process, ensures a high transport efficiency and minimizes the aerosol dispersion during transport of entrained particles through the transport tubing and upon mixing of the He carrier gas flow with Ar make-up gas flow in a co-axial mixing bulb prior to on-axis introduction into the ICP torch injector. The compression of the aerosol particles in an optimized space and time window results in an increase of the mass flux into the ICP, which is accompanied by an enhancement in sensitivity and throughput. In combination with a low-dispersion ablation cell housed in a LA-unit equipped with a nanosecond 1 kHz lasing system, a highly linear response of the integrated 238 U + signal intensity was observed upon ablation of a NIST SRM 610 glass as a function of the laser repetition rate up to 1 kHz. Single pulse responses with a full peak width at 50%, 10% and 1% of the maximum peak height of only 0.3 ± 0.1 (FWHM), 0.5 ± 0.1 (FW0.1M) and 1.2 ± 0.1 ms (FW0.01M) can be achieved. These peak profiles are closely approaching profiles generated in single particle-ICP-MS for individual metallic nanoparticles and microplastics.